A STUDY ON THE ABILITY IN WRITING DESCRIPTIVE TEXT BY THE SECOND YEAR STUDENTS OF MA DARUL QUR`AN - Meilizah Putri; Eliwarti Eliwarti; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This descriptive research aimed to find out the ability level of the second year students of MA Darul Quran in writing descriptive texts. The subjects of this study were the second year students of MA Darul Quran who were selected by using the cluster random sampling technique. 32 students employed in this study was used the Writing Test adapted by Brown in 2003. The results of the data analysis showed that the mean score of the students` ability in writing the descriptive text was 56. It can be stated that the ability of the second year students of MA Darul Quran in writing descriptive texts was average. Based on the result of the students’ ability in each writing aspect, the lowest score was in the grammar aspect and the highest score is in the content aspect.Key Words: Study, Writing Ability, Descriptive Text